Uncertainty and the Heterogeneous Capital Good Model - Ross, Stephen A. (Review of Economic Studies, 1975)
Journal Article Uncertainty and the Heterogeneous Capital Good Model Get access Stephen A. Ross Stephen A. Ross University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 1, January 1975, Pages 133–146, https://doi.org/10.2307/2296827 Published: 01 January 1975